2007
DOI: 10.1164/rccm.200610-1426oc
|View full text |Cite
|
Sign up to set email alerts
|

Control of Virus Reactivation Arrests Pulmonary Herpesvirus-induced Fibrosis in IFN-γ Receptor–deficient Mice

Abstract: Rationale: Idiopathic pulmonary fibrosis (IPF) is a chronic progressive fibrotic lung disorder of unknown cause. Several studies suggest an association between Epstein-Barr virus pulmonary infection and the development of IPF. Objectives: To determine whether reduction of ␥-herpesvirus reactivation from latency would alter progressive lung fibrogenesis in an animal model of virus-induced pulmonary fibrosis. Methods: IFN-␥ receptor-deficient (IFN-␥R؊/؊ ) mice infected intranasally with murine ␥-herpesvirus 68 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
112
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(117 citation statements)
references
References 49 publications
4
112
1
Order By: Relevance
“…Although gHV-68 infection is not identical to infection with EBV or HHV-8, and FITC inoculation does not recapitulate all aspects of IPF fibrogenesis, this model can be used to better understand particular cell types or profibrotic factors critical to virus-induced augmentation of fibrosis. The studies by Mora and colleagues in Th2-biased mice suggested that antiviral therapies may improve fibrotic outcomes by limiting viral reactivation (13). In contrast, our studies suggest that viral reactivation is not critical to the augmentation of fibrosis in wild-type mice at least during early latency; thus, antiviral drugs may not be as effective as previously hoped.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Although gHV-68 infection is not identical to infection with EBV or HHV-8, and FITC inoculation does not recapitulate all aspects of IPF fibrogenesis, this model can be used to better understand particular cell types or profibrotic factors critical to virus-induced augmentation of fibrosis. The studies by Mora and colleagues in Th2-biased mice suggested that antiviral therapies may improve fibrotic outcomes by limiting viral reactivation (13). In contrast, our studies suggest that viral reactivation is not critical to the augmentation of fibrosis in wild-type mice at least during early latency; thus, antiviral drugs may not be as effective as previously hoped.…”
Section: Discussioncontrasting
confidence: 69%
“…In addition, we have recently shown that lytic gHV-68 infection can exacerbate established pulmonary fibrosis (11). The mechanisms identified to contribute to lytic virus-induced exacerbation of fibrosis have included Th2 bias, persistent reactivation, alternative activation of macrophages, and fibrocyte recruitment (11)(12)(13).…”
mentioning
confidence: 99%
“…Ϫ/Ϫ mice were treated with the viral DNA polymerase inhibitor cidofovir (25,26). We identified a dosage (8 mg/kg) that effectively reduced MHV68 lung titers to wild-type levels (Fig.…”
Section: Cd8mentioning
confidence: 99%
“…These infected animals develop progressive lung fibrosis that shares common features observed in IPF lungs, including patchy and subpleural fibrosis, high levels of transforming growth factor (TGF)-␤ production, the presence of myofibroblast transformation, hyperplasia and epithelial mesenchymal transition of alveolar epithelial cells, and the activation of alveolar macrophages by the alternative pathway. [15][16][17][18] Our previous studies demonstrated that lytic replication in the chronic phase of infection is critical for fibrotic progression in IFN␥R Ϫ/Ϫ mice infected with MHV68. The administration of the antiviral drug cidofovir starting at 45 days post infection (dpi) reduced virus replication and halted fibrotic progression.…”
mentioning
confidence: 99%
“…The administration of the antiviral drug cidofovir starting at 45 days post infection (dpi) reduced virus replication and halted fibrotic progression. 16 Infection with a recombinant MHV68 that lacks v-cyclin, a gene that functions to control reactivation, developed vasculitis and fibrosis at the onset of the chronic phase (day 15) but failed to drive fibrosis in the late chronic phase (day 150). 16,19 In C57BL/6 mice, lytic MHV68 infection has been used as a cofactor to exacerbate established pulmonary fibrosis.…”
mentioning
confidence: 99%